Frontal cortex pyramidal neuron expression profiles differentiate the prodromal stage from progressive degeneration across the Alzheimer's disease spectrum - Labuza, Amanda; Alldred, Melissa J.; Pidikiti, Harshitha; Malek‐Ahmadi, Michael H.; Lee, Sang Han; Heguy, Adriana; Coleman, Paul D.; Chakrabarty, Souparna; Chiosis, Gabriela; Mufson, Elliott J.; Ginsberg, Stephen D. (Alzheimer's & dementia, 2025)
INTRODUCTION Underlying causes of Alzheimer's disease (AD) remain unknown, making it imperative to identify molecular mechanisms driving the pathobiology of AD onset and progression. METHODS Laser capture microdissection was used to isolate layer III pyramidal neurons from post mortem human prefrontal cortex (Brodmann area 9). Single population RNA sequencing was conducted using tissue from subjects with no cognitive impairment (NCI), mild cognitive impairment (MCI), and AD. Differentially expressed genes (DEGs) were compared across groups. RESULTS DEGs increased from prodromal (MCI vs. NCI) to progression (AD vs. MCI) to frank AD (AD vs. NCI). The majority of DEGs and pathways shared between prodromal and progression exhibited a change in the direction of dysregulation unlike pathways between progression and frank AD. DISCUSSION Candidate genes and pathways were identified that demarcate early‐stage AD onset from AD progression, providing a roadmap to study cortical cellular vulnerability and key targets for intervention at early stages of AD. Highlights Pyramidal neuron differentially expressed genes (DEGs) are directionally divergent between prodromal, progression, and frank Alzheimer's disease (AD). Pyramidal neuron DEGs are directionally convergent between progression and frank AD. Dysfunctional bioenergetic pathways increased dysregulation as the AD spectrum progressed. Immune response pathways were more dysregulated in frank AD than prodromal stages. DEGs, = biological pathways, and interactomes demarcate specific stages across the AD spectrum.